TECHNIQUE FOR ENHANCING STUDENTS' ORAL SPEECH USING A COGNITIVE APPROACH - Feruza Askarjanovna ALIMOVA (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article explores an innovative method for enhancing the oral speech capabilities of students through a cognitive approach. Recognizing the importance of effective communication skills in academic and professional contexts, the study integrates cognitive theories to develop a framework that fosters critical thinking, active engagement, and self-reflection in speech practice. By employing techniques such as interactive discussions, role-playing, and peer feedback, the method aims to improve students' fluency, pronunciation, and overall confidence in public speaking. The research involves a mixed-methods design, incorporating quantitative assessments of speech performance and qualitative feedback from participants.